Rancang Bangun Alat Pengupas Pinang Otomatis Berbasis Arduino Mega - Umirza Fadjar Arpan; Yosi Riduas Hais; Haerul Pathoni (Journal of Electrical Power Control and Automation (JEPCA), 2022)
Stripping the betel nut using a machine is considered to be more effective than manually, based on this I designed an automatic betel nut peeler control device using Arduino Mega as a mechanical and electrical system controller. In the design of this tool using a hollow iron frame material with 40X40 mm, with a length of 130 cm and a width of 30 cm. Furthermore, this tool is planned to be able to work with a capacity of 20 Kg/hour. After all components are completed, it will proceed to the tool development process to be able to perform performance tests. After testing, stripping using the manual method takes a relatively longer time, which is 11 minutes. While using the machine only takes 6 minutes. In this test, 1 kg or 74 young betel nut, yellow areca nut, dry areca nut, and wet old areca nut were used.